Lithium titanate coating diaphragm and preparation method thereof

By using a coating separator with synergistic effect of lithium titanate and polyacrylonitrile in lithium-ion batteries, the problems of lithium dendrites growth and SEI film instability are solved, efficient ionic conductivity and adhesion are achieved, and the safety and performance of lithium metal batteries are improved.

CN119864592APending Publication Date: 2025-04-22HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510036667.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The negative electrode of lithium-ion batteries has problems such as lithium dendrites growth, SEI film instability, and volume expansion effects, which limit the practical application of lithium metal batteries.

Method used

The coating membrane with synergistic effect of lithium titanate (LTO) and polyacrylonitrile (PAN) is used to improve the ionic conductivity through the introduction of lithium titanate, and the adhesion and wettability of the membrane are improved through the introduction of polyacrylonitrile.

Benefits of technology

The excellent performance of the coated diaphragm is achieved, including high ionic conductivity, good adhesion and wetting properties, preventing lithium dendrites from punctured through the diaphragm, and avoiding safety issues such as short circuits and thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864592A_ABST
    Figure CN119864592A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium titanate coating diaphragm and a preparation method thereof, the lithium titanate coating diaphragm comprises a base membrane and a coating on the base membrane, and the coating comprises polyacrylonitrile, lithium titanate and sodium dodecyl benzene sulfonate. The preparation method of the lithium titanate coating diaphragm comprises the following steps: coating a base diaphragm with composite slurry to obtain a coating diaphragm precursor, and performing extraction and dehydration treatment to obtain the lithium titanate coating diaphragm. Through the synergistic effect of lithium titanate and polyacrylonitrile, various properties of the coating diaphragm are excellent, good ionic conductivity is brought to the coating diaphragm through introduction of lithium titanate, meanwhile, lithium titanate is hard ceramic particles, lithium dendrites can be prevented from puncturing the diaphragm from the physical level by means of the high mechanical strength of the lithium titanate, and the performance of the coating diaphragm is improved. Safety problems such as short circuit and thermal runaway are prevented; the introduction of the fluoride-free polyacrylonitrile synergistically improves the wettability of the diaphragm, brings good adhesion to the coating diaphragm, and prevents the coating from falling off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium titanate coating separator and a preparation method thereof. Background Art

[0002] With the rapid development of social economy and the continuous improvement of people's demand for quality of life, relying on traditional fossil fuels for energy supply can no longer meet the needs of actual production. It is necessary to find environmentally friendly, low-cost renewable clean energy and design efficient energy storage devices. At present, lithium resources are relatively abundant, and the low reduction potential, light weight and small ion radius of lithium enable lithium-based batteries to have high battery potential, high volume, mass capacity and power density. These advantages enable lithium-ion batteries to dominate consumer batteries, power batteries and large-scale energy storage for many years to come.

[0003] When the lithium negative electrode and the electrolyte come into contact, a reaction occurs immediately, and a passivation layer (SEI film) is formed on the surface. This passivation layer is beneficial to improving battery performance, but the negative electrode of lithium-ion batteries has problems such as lithium dendrite growth, SEI film instability, and volume expansion effect, which in turn limits the practical application of lithium metal batteries. To address these problems, researchers often use ceramic materials such as high-strength and high-hardness ceramic particles (alumina, titanium oxide) for modification, but the prepared diaphragms usually have low ion conductivity. Summary of the invention

[0004] In view of the deficiencies of the prior art, an object of the present invention is to provide a lithium titanate coated diaphragm.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned lithium titanate coating diaphragm.

[0006] Another object of the present invention is to provide a composite slurry.

[0007] The purpose of the present invention is achieved through the following technical solutions.

[0008] A lithium titanate coated diaphragm comprises: a base film and a coating on the base film, wherein the coating comprises: polyacrylonitrile (PAN), lithium titanate (LTO) and sodium dodecylbenzene sulfonate, and the ratio of polyacrylonitrile (PAN), lithium titanate (LTO) and sodium dodecylbenzene sulfonate is (0.8-2.5):(5-30):(0.1-1) by mass.

[0009] In the above technical solution, the ratio of polyacrylonitrile (PAN), lithium titanate (LTO) and sodium dodecylbenzene sulfonate is preferably (1.5-2.5):(22-26):(0.5-0.8) by mass.

[0010] In the above technical solution, the lithium titanate coated diaphragm also includes conductive carbon black. In terms of mass fractions, the ratio of lithium titanate (LTO), sodium dodecylbenzene sulfonate and conductive carbon black is (5-30): (0.1-1): (1.5-5).

[0011] In the above technical solution, the ratio of lithium titanate (LTO), sodium dodecylbenzene sulfonate and conductive carbon black is preferably (22-26): (0.5-0.8):3 in parts by mass.

[0012] In the above technical solution, the method for obtaining lithium titanate (LTO) comprises the following steps:

[0013] Step 1, mixing a lithium source, a titanium source and a first solvent until uniform, to obtain a solution A, wherein the ratio of lithium in the lithium source to titanium in the titanium source is (4.2-4.8):(4.8-5.3) in terms of molar fractions;

[0014] In step 1, the first solvent is one or a mixture of isopropanol, acetone and anhydrous ethanol.

[0015] In step 1, the lithium source is one or a mixture of lithium hydroxide and lithium carbonate.

[0016] In step 1, the titanium source is one or a mixture of titanium dioxide, titanium tetrabromide and tetrabutyl titanate.

[0017] In step 1, the ratio of the total mass of the lithium source and the titanium source to the mass of the first solvent is (30-80):

[0018] (160~240).

[0019] Step 2: ball-mill the solution A until it is uniform, dry it to obtain a white powder, and calcine the white powder at 750-1000° C. for 8-24 hours under a nitrogen or inert gas atmosphere to obtain lithium titanate.

[0020] In step 2, the ball milling time is 8 to 14 hours, and the ball-to-material ratio of the ball milling is (10 to 30): (0.2 to 1.5).

[0021] In step 2, the drying temperature is 40-70° C., and the drying time is 14-18 hours.

[0022] The preparation method of the lithium titanate coating diaphragm comprises: coating the composite slurry on the base film to obtain the coating diaphragm precursor, extracting and dehydrating to obtain the lithium titanate coating diaphragm.

[0023] In the above technical solution, the dehydration treatment includes: drying at 50-70° C. for 6-12 minutes.

[0024] In the above technical solution, the extraction uses an extraction liquid, and the coating membrane precursor is sequentially subjected to extraction liquids with extractant concentrations from high to low, and the extractant is N-methylpyrrolidone (NMP).

[0025] In the above technical scheme, the extracting liquids with extractant concentrations from high to low are the first extracting liquid, the second extracting liquid, the third extracting liquid and the fourth extracting liquid, respectively. The first extracting liquid, the second extracting liquid and the third extracting liquid are mixtures of extracting liquid and water, and the fourth extracting liquid is water. Among them, the concentration of the extracting liquid in the first extracting liquid is 65-80wt%, the concentration of the extracting liquid in the second extracting liquid is 40-60wt%, and the concentration of the extracting liquid in the third extracting liquid is 20-40wt%.

[0026] A composite slurry comprises polyacrylonitrile (PAN), lithium titanate (LTO), sodium dodecylbenzene sulfonate and a slurry solvent. The ratio of polyacrylonitrile (PAN), lithium titanate (LTO) and sodium dodecylbenzene sulfonate is (0.8-2.5):(5-30):(0.1-1) by weight.

[0027] In the above technical solution, the ratio of polyacrylonitrile (PAN), lithium titanate (LTO) and sodium dodecylbenzene sulfonate is preferably (1.5-2.5):(22-26):(0.5-0.8) by mass.

[0028] In the above technical solution, the solid content of the composite slurry is 16-32wt%, preferably 29-30wt%.

[0029] In the above technical solution, the slurry solvent is N-methylpyrrolidone or a mixture of N-methylpyrrolidone and substance A, and substance A is a mixture of one or both of acetonitrile and N,N-dimethylformamide.

[0030] The method for preparing the above-mentioned composite slurry comprises: mixing a polyacrylonitrile (PAN) solution and a lithium titanate (LTO) solution until they are uniform to obtain a composite slurry, wherein the polyacrylonitrile (PAN) solution is a mixture of polyacrylonitrile (PAN) and a second solvent, and the lithium titanate (LTO) solution comprises: lithium titanate (LTO), sodium dodecylbenzene sulfonate and a third solvent, and the ratio of polyacrylonitrile (PAN) in the polyacrylonitrile (PAN) solution, lithium titanate (LTO) in the lithium titanate (LTO) solution and sodium dodecylbenzene sulfonate in the lithium titanate (LTO) solution is (0.8-2.5):(5-30):(0.1-1) by weight.

[0031] In the above technical solution, the ratio of polyacrylonitrile in the polyacrylonitrile solution, lithium titanate in the lithium titanate solution and sodium dodecylbenzene sulfonate in the lithium titanate solution is preferably (1.5-2.5):(22-26):(0.5-0.8) by mass.

[0032] In the above technical scheme, the method for obtaining polyacrylonitrile (PAN) solution is: polyacrylonitrile powder and a second solvent are mixed until uniform to obtain a polyacrylonitrile (PAN) solution, and the ratio of polyacrylonitrile powder to the second solvent is (8-15): (85-92) by mass.

[0033] In the method for obtaining a polyacrylonitrile (PAN) solution, the second solvent is N-methylpyrrolidone (NMP).

[0034] In the method for obtaining a polyacrylonitrile (PAN) solution, polyacrylonitrile powder and a second solvent are mixed, and stirred at 60 to 110° C. and a rotation speed of 400 to 500 r / min for 2 to 6 hours until the mixture is uniform.

[0035] In the above technical scheme, the method for obtaining a lithium titanate (LTO) solution is: lithium titanate (LTO), sodium dodecylbenzene sulfonate, conductive carbon black and a third solvent are mixed until uniform to obtain a lithium titanate (LTO) solution, wherein the ratio of lithium titanate (LTO), sodium dodecylbenzene sulfonate, conductive carbon black and the third solvent is (5-30): (0.1-1): (1.5-5): (64-93.4) ​​by mass.

[0036] In the above technical solution, the ratio of lithium titanate (LTO), sodium dodecylbenzene sulfonate, conductive carbon black and the third solvent is preferably (25-30): (0.7-1): 3: (64-70) by mass.

[0037] In the method for obtaining a lithium titanate (LTO) solution, lithium titanate (LTO), sodium dodecylbenzene sulfonate, conductive carbon black and a third solvent are mixed and wet-milled for 3 to 5 hours until uniform to obtain a lithium titanate (LTO) solution, wherein the wet-milling uses 5 to 10 mm zirconia balls, the ball-to-material ratio is (0.8 to 1.2): (6 to 8), the wet-milling revolution speed is 180 to 250 r / min, and the wet-milling rotation speed is 550 to 650 r / min.

[0038] In the method for obtaining a lithium titanate (LTO) solution, the third solvent is one or a mixture of several of N-methylpyrrolidone, acetonitrile and N,N-dimethylformamide.

[0039] In the above technical solution, polyacrylonitrile (PAN) solution and lithium titanate (LTO) solution are mixed and stirred at 20-45° C. until they are uniform to obtain a composite slurry.

[0040] In the above technical solution, polyacrylonitrile (PAN) solution and lithium titanate (LTO) solution are mixed, stirred at 20-45° C. at a speed of 200-400 r / min for 3-5 hours until uniform, to obtain a composite slurry.

[0041] The application of polyacrylonitrile, lithium titanate and sodium dodecylbenzene sulfonate to synergistically improve the ionic conductivity, membrane adhesion and / or breakdown voltage of the separator.

[0042] Application of polyacrylonitrile, lithium titanate and sodium dodecylbenzene sulfonate to synergistically improve the heat resistance and / or wettability of the separator.

[0043] Application of polyacrylonitrile, lithium titanate and sodium dodecylbenzene sulfonate to synergistically improve the liquid absorption rate and / or liquid retention rate of the diaphragm.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The present invention achieves excellent performance of the coating diaphragm through the synergistic effect of lithium titanate (LTO) and polyacrylonitrile. The introduction of lithium titanate (LTO) brings good ion conductivity to the coating diaphragm. At the same time, lithium titanate (LTO) is a hard ceramic particle. Relying on its strong mechanical strength, it can physically prevent lithium dendrites from piercing the diaphragm, preventing short circuit, thermal runaway and other safety problems. The introduction of non-fluorinated polyacrylonitrile (as a binder) synergistically improves the wettability of the diaphragm and brings good bonding force to the coating diaphragm to prevent the coating from falling off.

[0046] 2. Sodium dodecylbenzene sulfonate is used as a dispersant when preparing the lithium titanate (LTO) solution, so that the lithium titanate (LTO) has good dispersibility and no agglomeration occurs. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 is the SEM image of lithium titanate (LTO);

[0048] Figure 2 is the XRD pattern of lithium titanate (LTO);

[0049] Figure 3 This is a SEM image (1.0KX) of the lithium titanate coating diaphragm prepared in Example 6;

[0050] Figure 4 This is the SEM image (5.0KX) of the lithium titanate coated diaphragm prepared in Example 6. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0052] In the following examples, the base film is a PE film.

[0053] In the following examples, water is deionized water.

[0054] In the following embodiments, the electrolyte is a mixture of an electrolyte and a solvent, the concentration of the electrolyte is 1 mol / L, the electrolyte is lithium hexafluorophosphate, the solvent is a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate, and the volume ratio of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate is 1:1:1.

[0055] Air permeability value: Place the membrane on a Japanese AsahiSeiko air permeability tester, test one point every 10 cm along the length direction of the membrane, test 10 points in total, and take the average value of the 10 points, which is the air permeability value;

[0056] Breakdown voltage: Lay the diaphragm flat on the test conductive plate, test 50 breakdown points, and the average value of the 50 breakdown points is the breakdown voltage;

[0057] Thermal shrinkage: Cut the diaphragm into 4cm×6cm size, measure the area change of the 4cm×6cm diaphragm in a 150℃ oven for 1h, and obtain the thermal shrinkage data;

[0058] Ionic conductivity: At room temperature and 100% RH, the diaphragm is immersed in the electrolyte and the ionic conductivity is measured by the AC impedance method;

[0059] Diaphragm adhesion: Cut the diaphragm into a shape of 25mm×60mm, stick 3M tape on the diaphragm, and use a tensile testing machine to tear the 3M tape and the diaphragm apart. The force used is the diaphragm adhesion.

[0060] Liquid absorption rate: weigh a 5cm×5cm diaphragm as m0, soak it in electrolyte and take it out, wipe the electrolyte on the surface with a non-woven cloth and weigh it as m1. The liquid absorption rate of the diaphragm is calculated by (m1-m0) / m0*100%.

[0061] Liquid retention rate: Soak a 5cm×5cm diaphragm in electrolyte and take it out. Use non-woven cloth to wipe off the electrolyte on the surface and weigh it as m2. After wiping off the electrolyte on the surface, place it in the air for 1 hour and weigh it as m3. The liquid retention rate of the diaphragm is calculated by (m2-m3) / m3*100%.

[0062] Liquid creeping: Take a 4cm×15cm diaphragm, place it vertically and immerse the bottom (length 1cm) in the electrolyte for 20min, 40min, and 60min. The length of the diaphragm wetted by the electrolyte after soaking for different times is the liquid creeping value of the coated diaphragm (characterizing the wettability).

[0063] Embodiments 1 to 5

[0064] A method for preparing a composite slurry comprises: mixing a polyacrylonitrile (PAN) solution and a lithium titanate (LTO) solution, stirring at 25°C at a speed of 350 r / min for 4 hours until the mixture is uniform, to obtain a composite slurry, wherein the solid content of the composite slurry is Y, the polyacrylonitrile (PAN) solution is a mixture of polyacrylonitrile (PAN) and a second solvent, the lithium titanate (LTO) solution comprises lithium titanate (LTO), sodium dodecylbenzene sulfonate and a third solvent, and the ratio of polyacrylonitrile (PAN) in the polyacrylonitrile (PAN) solution, lithium titanate (LTO) in the lithium titanate (LTO) solution and sodium dodecylbenzene sulfonate in the lithium titanate (LTO) solution is X in parts by mass.

[0065] The method for obtaining a polyacrylonitrile (PAN) solution is as follows: polyacrylonitrile powder and a second solvent are mixed, and stirred at 80°C and a speed of 450 r / min for 3 hours until uniform, to obtain a polyacrylonitrile (PAN) solution, wherein the ratio of the polyacrylonitrile powder to the second solvent is 10:90 by mass, and the second solvent is N-methylpyrrolidone (NMP).

[0066] The method for obtaining a lithium titanate (LTO) solution is as follows: lithium titanate (LTO), sodium dodecylbenzene sulfonate, conductive carbon black and a third solvent are mixed, and wet ball milling is performed for 4 hours until the mixture is uniform to obtain a lithium titanate (LTO) solution. The ratio of lithium titanate (LTO), sodium dodecylbenzene sulfonate, conductive carbon black and the third solvent is Z by weight, wherein the wet ball milling uses 8 mm zirconium oxide balls, the ball-to-material ratio is 1:7, the revolution speed of the wet ball milling is 200 r / min, the rotation speed of the wet ball milling is 600 r / min, and the third solvent is N-methylpyrrolidone. The method for obtaining lithium titanate (LTO) comprises the following steps:

[0067] Step 1, mixing a lithium source, a titanium source and a first solvent until uniform, to obtain a solution A, wherein, in terms of the amount of substance, the ratio of lithium in the lithium source to titanium in the titanium source is 4.4:5.0, the first solvent is isopropanol, the lithium source is lithium carbonate, the titanium source is titanium dioxide (powder), and the ratio of the total mass of the lithium source and the titanium source to the mass of the first solvent is 73.935:180;

[0068] Step 2, placing solution A in a ball mill and milling at high speed for 12 hours until uniform, drying in a 60° C. forced air drying oven for 16 hours to obtain a white powder, and calcining the white powder at 950° C. for 16 hours under a nitrogen atmosphere to obtain lithium titanate (powder), wherein the ball-to-material ratio of the ball mill is 15:1, and the particle size of the lithium titanate (powder) is D90=1.03 μm.

[0069] The values ​​of X, Y and Z are shown in Table 1.

[0070] Table 1

[0071] Composite slurry X Y Z Example 1 2:24:0.64 29.04wt% 30:0.8:3:66.2 Example 2 2:16:0.64 21.04wt% 20:0.8:3:66.2 Example 3 2:24:0.48 28.88wt% 30:0.6:3:66.4 Example 4 1:9:0.24 27.85wt% 30:0.8:3:66.2 Example 5 1:21:0.45 30.23wt% 30:0.8:3:66.2

[0072] Embodiments 6 to 10

[0073] A method for preparing a lithium titanate coating diaphragm comprises: coating a composite slurry on a base film to obtain a coating diaphragm precursor, extracting, and dehydrating (drying in an oven at 60° C. for 10 minutes) to obtain a lithium titanate coating diaphragm, wherein the extraction adopts an extracting liquid, the coating diaphragm precursor passes through extracting liquids with extractant concentrations from high to low in sequence, the extracting liquid is N-methylpyrrolidone (NMP), and the extracting liquids with extractant concentrations from high to low are successively a first extracting liquid, a second extracting liquid, a third extracting liquid, and a fourth extracting liquid, the first extracting liquid, the second extracting liquid, and the third extracting liquid are each a mixture of an extracting liquid and water, the fourth extracting liquid is water, the concentration of the extracting liquid in the first extracting liquid is 70wt%, the concentration of the extracting liquid in the second extracting liquid is 50wt%, and the concentration of the extracting liquid in the third extracting liquid is 30wt%. The composite slurry is one of Examples 1 to 5.

[0074] Table 2

[0075] Lithium titanate coated diaphragm Composite slurry used in preparing lithium titanate coating diaphragm Example 6 Example 1 Example 7 Example 2 Example 8 Example 3 Example 9 Example 4 Example 10 Example 5

[0076] Comparative Example 1

[0077] A method for preparing LTO slurry comprises: mixing the lithium titanate (powder), conductive carbon black and NMP prepared in Example 1, and wet-milling them for 4 hours until they are uniform, wherein the ratio of lithium titanate (LTO), conductive carbon black and NMP is 30:3:66.2 by mass, wherein 8 mm zirconia balls are used in the wet ball milling, the ball-to-material ratio is 1:7, the orbital speed of the wet ball mill is 200 r / min, and the rotation speed of the wet ball mill is 600 r / min.

[0078] The LTO slurry of Comparative Example 1 agglomerated in large pieces during the preparation process.

[0079] Comparative Example 2

[0080] A method for preparing a coated diaphragm is basically the same as that of Example 6, except that the "composite slurry" is replaced by the "lithium titanate (LTO) solution prepared in Example 1".

[0081] The coated diaphragm of Comparative Example 2 fell off during the extraction process and could not be used.

[0082] Comparative Example 3

[0083] A method for preparing a coated diaphragm is basically the same as that in Example 6, except that the composite slurry is different. The method for preparing the composite slurry used in the coated diaphragm of Comparative Example 3 comprises: mixing the polyacrylonitrile (PAN) solution in Example 1 and the lithium titanate (LTO) solution in Example 1, stirring at 25°C at a speed of 350 r / min for 4 hours until uniform, to obtain a composite slurry, the solid content of the composite slurry is 32.61wt%, and the ratio of polyacrylonitrile (PAN) in the polyacrylonitrile (PAN) solution, lithium titanate (LTO) in the lithium titanate (LTO) solution, and sodium dodecylbenzene sulfonate in the lithium titanate (LTO) solution is 0.5:29.5:0.24 by mass.

[0084] The lithium titanate coated diaphragms prepared in Examples 6 to 10 and the coated diaphragm prepared in Comparative Example 3 were subjected to air permeability test, breakdown voltage test, thermal shrinkage test, ion conductivity test and adhesion test, and the air permeability value, breakdown voltage, thermal shrinkage rate, ion conductivity and membrane adhesion were obtained in turn. The test results are shown in Table 3.

[0085] Table 3

[0086]

[0087] Through the above tests, it can be seen that the synergy of polyacrylonitrile and LTO can make the lithium titanate coating diaphragm have excellent air permeability, breakdown voltage, thermal shrinkage performance and ionic conductivity, so that the diaphragm has more stable performance. Combined with the diaphragm of Comparative Example 2 (without adding polyacrylonitrile), there is a slight drop of material during the preparation process, which also proves from the side that the introduction of polyacrylonitrile has a great improvement in the adhesion of the diaphragm. Through Comparative Example 3, it can be seen that when a small amount of polyacrylonitrile is added to the coating slurry, the performance of the diaphragm is relatively poor.

[0088] The lithium titanate coating diaphragms prepared in Examples 6 to 10 and the coating diaphragm prepared in Comparative Example 3 were subjected to liquid absorption, liquid climbing and liquid retention tests, and the obtained data are shown in Table 4.

[0089] Table 4

[0090]

[0091] Through the liquid absorption, liquid retention and liquid climbing tests, it can be seen that the introduction of LTO and polyacrylonitrile in an appropriate proportion can bring better electrolyte wettability to the diaphragm and better preserve the electrolyte in the battery.

[0092] Figure 1 This is a SEM image of lithium titanate (LTO). It can be seen that the LTO powder is spherical and the prepared lithium titanate is uniform in size with a particle size of about 1 μm.

[0093] Figure 2XRD pattern of lithium titanate (LTO) Figure 2 In the figure, "0.0e+000" represents the baseline of the test, "2.0e+003" represents 2000cps, "4.0e+003" represents 4000cps, "6.0e+003" represents 6000cps, and "8.0e+003" represents 8000cps). It can be seen that LTO has a good performance on the (1, 1, 1) plane. Figure 2 The characteristic peak of "【1】" in the figure is greater than 8000cps, which proves that LTO presents a relatively complete crystal form. At the same time, there are no impurity peaks and no interference, which proves that the purity of LTO is relatively high.

[0094] Figure 3 This is a SEM image (1.0KX) of the lithium titanate coating diaphragm prepared in Example 6; Figure 4 This is the SEM image (5.0KX) of the lithium titanate coating diaphragm prepared in Example 6. It can be observed that the coating prepared under this ratio is relatively evenly distributed.

[0095] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A lithium titanate coated diaphragm, characterized in that: include: The base film and the coating on the base film include polyacrylonitrile, lithium titanate and sodium dodecylbenzene sulfonate. The ratio of polyacrylonitrile, lithium titanate and sodium dodecylbenzene sulfonate is (0.8-2.5):(5-30):(0.1-1) by weight.

2. The lithium titanate coated diaphragm according to claim 1, characterized in that: The method for obtaining lithium titanate comprises the following steps: Step 1, mixing a lithium source, a titanium source and a first solvent until uniform, to obtain a solution A, wherein the ratio of lithium in the lithium source to titanium in the titanium source is (4.2-4.8):(4.8-5.3) in terms of molar fractions; Step 2: ball-mill the solution A until it is uniform, dry it to obtain a white powder, and calcine the white powder at 750-1000° C. for 8-24 hours under a nitrogen or inert gas atmosphere to obtain lithium titanate.

3. The lithium titanate coated diaphragm according to claim 1, characterized in that: The lithium titanate coating diaphragm also includes conductive carbon black. The ratio of lithium titanate, sodium dodecylbenzene sulfonate and conductive carbon black is (5-30): (0.1-1): (1.5-5) by weight.

4. The method for preparing a lithium titanate coating diaphragm according to any one of claims 1 to 3, characterized in that: include: The slurry is coated on a base film to obtain a coating membrane precursor, and then extracted and dehydrated to obtain a lithium titanate coating membrane.

5. A composite slurry, characterized in that: include: Polyacrylonitrile, lithium titanate, sodium dodecylbenzene sulfonate and slurry solvent, calculated by weight, the ratio of polyacrylonitrile, lithium titanate and sodium dodecylbenzene sulfonate is (0.8-2.5):(5-30):(0.1-1).

6. The composite slurry according to claim 5, characterized in that: The solid content of the composite slurry is 16-32wt%.

7. A method for preparing the composite slurry according to any one of claims 5 to 6, characterized in that: include: The polyacrylonitrile solution and the lithium titanate solution are mixed until uniform to obtain a composite slurry, wherein the polyacrylonitrile solution is a mixture of polyacrylonitrile and a second solvent, and the lithium titanate solution includes: lithium titanate, sodium dodecylbenzene sulfonate and a third solvent, and the ratio of polyacrylonitrile in the polyacrylonitrile solution, lithium titanate in the lithium titanate solution and sodium dodecylbenzene sulfonate in the lithium titanate solution is (0.8-2.5):(5-30):(0.1-1) by mass.

8. Application of polyacrylonitrile, lithium titanate and sodium dodecylbenzene sulfonate to synergistically improve the ionic conductivity, membrane adhesion and / or breakdown voltage of the separator.

9. Application of polyacrylonitrile, lithium titanate and sodium dodecylbenzene sulfonate to synergistically improve the heat resistance and / or wettability of the separator.

10. The application of polyacrylonitrile, lithium titanate and sodium dodecylbenzene sulfonate to synergistically improve the liquid absorption rate and / or liquid retention rate of the diaphragm.

Citation Information

Patent Citations

  • Preparation method of graphene-polypyrrole-lithium titanate negative electrode material of lithium battery

    CN104037395A

  • Preparation method of lithium titanate and polyaniline composite with good rate capability

    CN106058182A

  • A separating membrane used for a lithium ion battery, a preparing method thereof and the lithium ion battery

    CN106558664A

  • Porous lithium metatitanate type lithium ion sieve and preparation method thereof

    CN119114005A